Implementation of enviromental impact assessment (EIA) on residential projects in Sarawak - Syarifah Noorlia, bt Wan Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Sarawak economic is expected to remain robust and dynamic which leads to urban migration and demands for more residential developments. The level and types of impact from residential projects will vary significantly based on project-to-project basis. New township on virgin sites can be extremely intrusive and have major impacts on natural resources and the existing natural environment. EIA is essentially a planning tool for preventing environmental problems due to an action. It is required under the Sarawak NREO 1993. Certain criteria on development of residential and commercial areas are prescribed activities that require ElA implementation. However, the problems faced by the authorities and developers may affect the implementation ofElA. The study aims at looking to the perception of the developers, authorities as well as the public on implementation of EIA. It involves collation of guidelines on housing developments, EIA and EMP reports, literature and other published articles on housing development. The study also conducted interviews with key personnel of the authorities and selected ElA consultants. The developers were concern on the procedural delays and red tape of an ElA approval. Approval from SPA is their major license to project implementation, although SPA only gives approval in principle. The authorities need more resources to cater the services as more development is coming. Some of the public are aware of ElA implementation. Respondents would choose price and promotion factor over environmental conditions of the area. Deficiencies in ElA reports can be reduced by giving more stress on important issues and have sound knowledge on the issues. NREB can work more efficiently giving more publicity to the public and define its roles and functions. SPA, NREB and Land and Survey Department working closely in giving approval to development can avoid future difficulties on the environment.